2018
DOI: 10.1007/s00244-018-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms, Neurological Signs, and Electrophysiological Findings in Surviving Residents with Probable Arsenic Exposure in Toroku, Japan

Abstract: Chronic arsenic intoxication is known to cause multisystem impairment and is still a major threat to public health in many countries. In Toroku, a small village in Japan, arsenic mines operated from 1920 to 1962, and residents suffered serious sequelae of arsenic intoxication. We have performed annual medical examinations of these residents since 1974, allowing us to characterize participants’ long-term health following their last exposure to arsenic. The participants could not be described as having “chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, it has been identified which arsenicderived oxidative stress to be strongly involved in acute renal damage. 11 The liver is another target organ of arsenic toxicity. 29 In the present study, cell necrosis with degeneration, severe hemorrhage, infiltration and formation of Kupffer cells nodules at the site of cellular destruction were recognized in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been identified which arsenicderived oxidative stress to be strongly involved in acute renal damage. 11 The liver is another target organ of arsenic toxicity. 29 In the present study, cell necrosis with degeneration, severe hemorrhage, infiltration and formation of Kupffer cells nodules at the site of cellular destruction were recognized in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…10 Neurological mechanisms are affected mainly due to exposure to arsenic. 11 In these cases, clinical signs of encephalopathy are presented with weakness, itching, hemolysis, thrill and fever. 6 So, it is important to understand the complications of arsenic-induced toxicity in target organs by more details.…”
Section: Introductionmentioning
confidence: 99%
“…At least 140 million people in more than 50 countries are exposed to As-contaminated drinking water [3]. However, although a small number of acute As exposure patients have been studied in detail, relatively few studies have been performed on a detailed neuropathy of patients chronically exposed to As [4,5,6]. Although patients with chronic As exposure are numerous, their symptoms and clinical courses remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, several studies have shown that arsenic exposure induces peripheral neuropathy or neuritis [7, 9, 22–24]. A few studies have separately analyzed the function of small and large fibers, and suggested that these particular effects of arsenic are specific to small fibers [6, 9, 10]. Large-fiber function can be evaluated not only by neurological examination of vibration sensation but also by nerve conduction studies.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the peripheral nervous system, a considerable number of patients who experience chronic arsenic exposure report subjective complaints of numbness or tingling [7, 10], but nerve conduction studies reveal no abnormal findings [11]. As for the central nervous system, the central sensory conduction time of patients with chronic arsenic exposure is longer than that in age-matched normal controls [6].…”
Section: Introductionmentioning
confidence: 99%